2001
DOI: 10.1016/s1097-2765(01)00174-5
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 Is Required for Homology-Directed Repair of Chromosomal Breaks

Abstract: The BRCA2 tumor suppressor has been implicated in the maintenance of chromosomal stability through a function in DNA repair. In this report, we examine human and mouse cell lines containing different BRCA2 mutations for their ability to repair chromosomal breaks by homologous recombination. Using the I-SceI endonuclease to introduce a double-strand break at a specific chromosomal locus, we find that BRCA2 mutant cell lines are recombination deficient, such that homology-directed repair is reduced 6- to >100-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
709
1
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 891 publications
(743 citation statements)
references
References 57 publications
27
709
1
6
Order By: Relevance
“…Interestingly, the formation of RAD51 foci after DNA damage was shown to be dependent upon functional BRCA2, a result that led to suggestions that BRCA2 is required for the recruitment of RAD51 to sites of DSBs, and thus for the cellular function of RAD51 (Sharan et al, 1997;Yuan et al, 1999). Consistent with this view, BRCA2-deficient murine and human cells exhibit a spontaneous genome instability phenotype that involves the accumulation of chromosome breaks and radial chromosomes, presumably due to defects in the repair of replicationassociated DSBs (Patel et al, 1998;Yu et al, 2000;Moynahan et al, 2001;Tutt et al, 2001).…”
Section: Regulation Of Recombination By Brca2mentioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly, the formation of RAD51 foci after DNA damage was shown to be dependent upon functional BRCA2, a result that led to suggestions that BRCA2 is required for the recruitment of RAD51 to sites of DSBs, and thus for the cellular function of RAD51 (Sharan et al, 1997;Yuan et al, 1999). Consistent with this view, BRCA2-deficient murine and human cells exhibit a spontaneous genome instability phenotype that involves the accumulation of chromosome breaks and radial chromosomes, presumably due to defects in the repair of replicationassociated DSBs (Patel et al, 1998;Yu et al, 2000;Moynahan et al, 2001;Tutt et al, 2001).…”
Section: Regulation Of Recombination By Brca2mentioning
confidence: 90%
“…The RAD51 nucleoprotein filament mediates a search for homology within the sister chromatid, which in turn serves as a template for DNA synthesis to restore any lost sequences at the break site and ultimately regenerate intact DNA (West, 2003;Sung and Klein, 2006). The tumour suppressor and breast cancer-susceptibility gene BRCA2 is required for normal levels of HR-mediated DSB repair (Yu et al, 2000;Moynahan et al, 2001), providing an important link between the ability of a cell to maintain genome stability and tumorigenesis.…”
Section: The Dual Functions Of Recombinationmentioning
confidence: 99%
“…Direct evidence of a role for BRCA1 and BRCA2 in HR came from quantifying recombinational repair of a site-specific DSB in BRCA mutant cell lines. Either BRCA1 or BRCA2 mutation reduces the efficiency of HR induced by a site-specific DSB [83][84][85][86][87]. Errorprone repair of the DSB by single strand annealing (SSA) is increased in BRCA2 mutants [87,88]-a pattern reminiscent of HR mutants in yeast and in other vertebrate cells.…”
Section: Role Of Brca1 and Brca2 In Hr Regulationmentioning
confidence: 99%
“…Extensive studies have indicated that BRCA2 has an important function in DNA repair (Connor et al, 1997;Mizuta et al, 1997;Sharan et al, 1997;Wong et al, 1997;Chen et al, 1998;Patel et al, 1998). Recent reports indicate that BRCA2 acts in the homology-directed recombinational repair of double-strand DNA breaks (Davies et al, 2001;Moynahan et al, 2001;Xia et al, 2001;Kraakman-van der Zwet et al, 2002). The finding that BRCA2 is mutated in Faconi anemia patients further indicates that BRCA2 functions in a DNA damage-repair pathway (Howlett et al, 2002).…”
Section: Introductionmentioning
confidence: 99%